Efeitos da infusão contínua de tiopental ou propofol em coelhos mantidos em respiração espontânea - Biteli, Eliselle Gouveia de Faria [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The effects of thiopental and propofol were comparatively evaluated about its influence on cardiovascular and respiratory parameters, blood gas, blood glucose levels, cell kinetics and recovery period in 20 rabbits of New Zealand White, adults, male and female, with weight between 3,67±0,43 Kg. After a random selection, they were shared into two groups of 10 animals, called propofol group (GP) and thiopental group (GT). For GP, general anesthesia was induced by intravenous (IV) administration of propofol (10 mg/Kg) and then began continuous infusion at an initial dose 1 mg/Kg/min, and then was adjusted as necessary to the bispectral index values vary between 65 and 75. The same method was employed for GT, using thiopental instead propofol, at the dose of 10 mg/Kg for induction followed the initial dose of 1 mg/Kg/min. Data collection of the variables of interest in both groups began 20 minutes after induction of anesthesia (M0) and new measurements were made at 15 minutes intervals for a period of 60 minutes. The assessment of recovery began 30 minutes (MR30) after the infusion of agents and new evaluations were made at intervals of 60 minutes. Data were analysed using to analysis of variance, two-way (two-way ANOVA) and route (One-way ANOVA) followed by Bonferroni test (p<0,05). For recovery assessment, the scores were analyzed and the groups were compared by non parametric Wilcoxon test for 2 independent samples (p<0,05). In GP, the partial pressure of oxygen (PaO2), carbon dioxide (PaCO2) and oxyhemoglobin saturation (SaO2) in arterial blood increased from M30 and M60, respectively. The tidal volume (VT) in M60, and respiratory index (IR) in M0, were lower in the GP, while the arterial oxygen content (CaO2) at M0 was greater in GP than in GT. The alveolar oxygen tension (PAO2), alveolar-arterial oxygen difference (P(A-a)O2), IR, arterial-alveolar ratio (PaO2/PAO2) and ratio of partial pressure of arterial oxygen to fraction of ...

Avaliaram-se, comparativamente, os efeitos do tiopental e do propofol sobre os parâmetros cardiovasculares, respiratórios, hemogasométricos, nível glicêmico, cinética celular e período de recuperação. Para tanto, utilizaram-se 20 coelhos da raça Nova Zelândia Branco, adultos, machos ou fêmeas, com peso médio de 3,67±0,43 Kg. Após seleção aleatória, estes foram distribuídos em dois grupos de 10 animais, denominados grupo propofol (GP) e grupo tiopental (GT). Para o GP, foi induzida a anestesia geral pela administração intravenosa (IV) de propofol (10 mg/Kg) e em seguida, iniciou-se a infusão contínua na dose inicial 1 mg/Kg/min, a qual, havendo necessidade, foi reajustada de modo a que o índice biespectral estivesse situado entre 65 e 75. Para o GT empregou-se a mesma metodologia, substituindo-se o propofol pelo tiopental. As observações das variáveis de interesse em ambos os grupos, tiveram início 20 minutos após a indução anestésica (M0) e novas mensurações foram realizadas em intervalos de 15 minutos, por um período de 60 minutos. A avaliação da recuperação teve início 30 minutos (MR30) após o término da infusão dos fármacos e novas avaliações foram realizadas em intervalos de 60 minutos. Os dados foram submetidos à análise de variância de duas vias (Two-way ANOVA) e uma via (One-way ANOVA), seguidas pelo teste de Bonferroni (p<0,05). Para a análise da recuperação, os escores foram analisados e os grupos comparados pelo teste não paramétrico de Wilcoxon de 2 amostras independentes (p<0,05). No GP, a pressão parcial de oxigênio (PaO2) o dióxido de carbono (PaCO2) e a saturação da oxihemoglobina (SaO2) no sangue arterial aumentaram a partir do M30 e no M60, respectivamente. O volume corrente (VT), no M60, e o índice respiratório (IR), no M0, foram menores no GP, enquanto o conteúdo arterial de oxigênio (CaO2), no M0, foi maior no GP que no GT. A pressão de oxigênio alveolar ...
Keywords: Coelho; Anestesia intravenosa; Sedativos; Tiopental; Propofol